2020
DOI: 10.1002/jmv.26556
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in people living with HIV: Clinical implications of dynamics of the immune response to SARS‐CoV‐2

Abstract: Background Little evidence on COVID‐19 in people living with HIV (PLWH) is currently available. Material and Methods We reported clinical and viro‐immunological data of all HIV‐positive patients admitted to our centre with COVID‐19 from March 1 to May 12 , 2020. Results Overall, five patients were included: all were virologically‐suppressed on antiretroviral therapy and CD4+ count was >350 cell/mm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 30 publications
8
35
1
5
Order By: Relevance
“…The ability of HIV/SARS-CoV-2 co-infection to cause excessive T cell activation has been observed in sample sets little in size ( D’Ettorre et al, 2020 , Gao et al, 2020 ). Besides, it has been detected that COVID-19 severe symptomatic manifestations may lead to a more pronounced T cell response than mild symptomatic clinical course ( Ho et al, 2020 , Mondi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of HIV/SARS-CoV-2 co-infection to cause excessive T cell activation has been observed in sample sets little in size ( D’Ettorre et al, 2020 , Gao et al, 2020 ). Besides, it has been detected that COVID-19 severe symptomatic manifestations may lead to a more pronounced T cell response than mild symptomatic clinical course ( Ho et al, 2020 , Mondi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ndings from other studies suggested that an impaired immune reactivity could contribute to low IgG positive [22]. Although this may suggest that PLWH may be more vulnerable with a SARS-CoV-2 infection, ndings from other studies have observed no increased risk and severity of COVID-19 in affected PLWH [23]. Regardless, the risk of increased PLWH vulnerability should not be ignored as the reported similarity in immune response may only apply to PLWH.…”
Section: Discussionmentioning
confidence: 93%
“…To date, the immunological impact of HIV on SARS-CoV-2 immune response has been mainly reported in isolated or limited cases of co-infection (d’Ettorre et al, 2020; Mondi et al, 2020; Wang et al, 2020). Only two studies have measured the effect of HIV-1 infection on the overall profile of T cells in COVID-19 cases: Karim et al .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the immunological impact of HIV on SARS-CoV-2 immune response has been mainly reported in isolated or limited cases of co-infection (d' Ettorre et al, 2020;Mondi et al, 2020;Wang et al, 2020). Only two studies have measured the effect of HIV-1 infection on the overall profile of T cells in COVID-19 cases: Karim et al showed that viraemic HIV-infected COVID-19 patients exhibited lower frequencies of tissue homing CXCR3+ CD8 T cells and higher T cell activation compared to HIV-uninfected patients (Karim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%